Intellectual Assets as an Object of International Standardization - G. V. Fokin (Informaciâ i Innovacii, 2025)
Purpose. To draw attention to the need for international standardization of intellectual assets to promote cross-border technological cooperation.Results. A review of the proposed tool for standardization of intellectual assets — the draft international standard of BRICS IP-Actives business practices IPM.2.001–2024 BRICS IPM.2.002–2024 ‘BRICS Innovation Entrepreneurship and Development. BRICS IP-Actives Business Practices Standards. Evidentiary recognition of intellectual property rights in the BRICS, EAEU, Russian Federation, SCO markets’. It is shown which international structures, on the basis of which approaches and through which procedures can carry out international standardization of intellectual assets.Conclusions. The necessity of wide discussion and adoption of the mentioned Standard in order to develop the international market of technologies, authorship and applicability of which are confirmed by the right confirming documents is proved.